PANGGUNG POLITIK KYAI NU DI KABUPATEN PASURUAN ANTARA MASLAHAH UMMAT DAN SYAHWAT POLITIK - Muhammad Nur Hadi; Miftachul Taubah; Syaifullah (Universitas Yudharta Pasuruan, 2019)
Research aims to understand the dialectic between structure and agency that puts clerics as individuals who are creative and have the capacity transformative to produce and reproduce the structure on one side of the inclined limit (limiting-disabling) and on the other hand enable (enabling) action, all done the kyai in his position as a religious elite. This theme is interesting because of the many NU clerics who are directly or indirectly involved in the political map that takes place in this country. While methodologically, this research will be designed with a qualitative approach considering the unit of study is a dynamic social phenomenon. The subjects in this study were determined purposively. The technique used in collecting data in this study was carried out in several ways such as in-depth interviews that were not structured orlong open-ended interviews. This study also uses data sources from the analysis of written materials (literature and documents). The analysis is carried out inductively by linking data, data categorization, data comparison, mutual data relations, data reduction, and drawing conclusions. The results of this study indicate that the majority of the kyai stated that NU and politics are two entities that are not diametric, both are related to one another. NU as jam'iyah ijtima'iyyah diniyyah must be rahmatan lil alamin, as well as control for political life. NU is a social organization, not a political organization. If NU has anything to do with the government, then it is only limited to the obligation as a people.